OS2.1 Incidence patterns for primary spinal cord ependymomas in adults: a Surveillance, Epidemiology, and End Results study. (6th September 2019) - Man, W; Wang, G
Abstract: BACKGROUND: Ependymomas are the most common primary spinal cord tumors in adults. However, few population-based studies analyzed the epidemiological features for this tumor type. We explored Surveillance, Epidemiology, and End Results (SEER) database to evaluate the incidence patterns over time with regard to patient gender, race, age at diagnosis, and histological subtype for patients diagnosed with primary malignant spinal cord gliomas between 1973 and 2015. METHODS: We queried SEER database to identify all adult patients (≥ 20 years of age) diagnosed with primary spinal cord ependymomas during 1973–2015. Variables of interest included gender, race, age at diagnosis, and histological subtype of tumor. The SEER*Stat 8.3.5 program was used to calculate frequencies, age-adjusted incidence rates (IR) with adjustment to the 2000 US Standard population and 95% confidence intervals (CI). An annual percentage change (APC) statistic with a 2-sided p-values was used to assess incidence patterns over time. RESULTS: 1224 adult patients with primary spinal cord ependymomas were diagnosed between 1973 and 2015. Of the total population, 55.7% were males (n = 682) and 44.3% were females (n=542). Myxopapillary ependymomas (ICD-O-3 code 9394), papillary ependymomas (9393), ependymomas (9391) and anaplastic ependymomas (9392) accounts for 28.7% (n = 351), 0.5% (n = 6), 69.4% (n = 849) and 1.5% (n = 18) respectively. The overall age-adjusted IR for all adult primary spinal cord ependymomas was 0.16 per 100, 000 (95%CI 0.15–0.17). The IR in male was higher than that in female (males 0.19 per 100, 000 [95% CI 0.17–0.20], females 0.14 per 100, 000 [95% CI 0.13–0.14]. Caucasians experienced higher IR (0.18 per 100, 000 [95% CI 0.17–0.19]) compared to African Americans (0.19 per 100, 000 [95% CI 0.07–0.12]) and the others (0.10 per 100, 000 [95% CI 0.08–0.13]). Patients of age between 40 and 49 years experienced the highest IR (0.25 per 100, 000 [95% CI 0.22–0.29]) than patients in the other age ranges. The most common histological subtypes were ependymomas (0.11 per 100, 000 [95% CI 0.11–0.12]) and myxopapillary ependymomas (0.047 per 100, 000 [95% CI 0.042–0.052]. The overall age-adjusted IR for all adult primary spinal cord ependymomas showed a statistically significant increase over time between 1973 and 2015 (APC=5.15, p<0.01). The same increasing trend was found in Caucasians (APC=5.36, p<0.01) and in both males (APC=5.13, p<0.01) and females (APC=4.95, p<0.01). CONCLUSION: This study demonstrates an increasing IR of adult primary spinal cord ependymomas over the past four decades. Males, Caucasians and age between 40 and 49 years experienced a higher IR.